Analisis Perubahan Perilaku Konsumen pada E-Commerce Shopee Selama Masa Pandemi Covid 19 (Studi Kasus Perilaku Konsumen E-Commerce Shopee di Kota Tasikmalaya) - Sunandar, Syifa Nurmaitsa Putri; Harmon Chaniago (International Journal Administration, Business & Organization, 2021)
Seeing the current situation and conditions, the presence of an epidemic that is in the spotlight of the world and is feared by everyone, namely Covid 19. Where people rush to stay at home so they can avoid this deadly outbreak. In Tasikmalaya there is a change in behavior shown from people who used to only buy goods offline so that people can see these items firsthand, the Covid Pandemic is the reason why there is a change in people's behavior. Today we are introduced to a technology that helps people to be able to buy a product or food without direct contact, namely by using a Shopee E-commerce, changes in shopee consumer behavior have been analyzed for the correctness by processing data using SPSS Version 22 by making a questions made on Google Forms by taking a sample, namely the City of Tasikmalaya, the area of ​​which is the city that has a change in behavior, especially in Shopee E-Commerce. This factor has been proven by the existence of a reference group factor and a status role factor that makes a change in behavior towards Shopee E-Commerce consumers in Tasikmalaya City.